Pattern of Breast Cancer in Women at Child-bearing Age, its Risk Factors and Clinicopathological Evaluation in Tertiary Level Hospital - Haque, Md Rasedul; Hossain, Md Amzad (Journal of Rangpur Medical College, 2024)
Background: Carcinoma breast is the leading cancer in female in Bangladesh, increasing significantly due to urbanization and adoption of western life style. Objective: This study aimed to systematically understand the pattern of breast cancer, its risk factors and clinicopathological evaluation in women at their childbearing age. Methods: A cross sectional observational study, data was collected from 50 patients of histopathologically confirmed breast cancer in the department of Surgery, Combined Military Hospital, Dhaka from 2022 to 2023. Results: The majority of the cases were 41-45(42%) years age with mean presentation was 43.55 (SD-/+9.63) years. Invasive ductal carcinoma was the most common subtype 86%, followed by ductal carcinoma in situ (8%). Of the cases 2% were nullipara and 46% had two children. Median age of at 1st birth was 21 years. A significant proportion (16%) had family history of breast cancer. 98% patients gave history of breast feeding. Conclusions: Breast cancer is increasingly occurring in younger age groups in Bangladesh, results suggested a mixture of different factors in women like age of menarche, age of first child birth, parity, history of breast feeding and family history poses higher risk for breast cancer. J Rang Med Col. March 2024; Vol. 9, No. 1:16-21